Purwarupa Sistem Pemantau dan Peringatan Kadar Gas Karbon Monoksida (CO) pada Kabin Mobil Berbasis Mikrokontroler ATMega8 - Anggit Perdana; Adian Fatchur Rochim; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2013)
High growth in vehicle, contribute air pollution and reduce human health quality. One of pollutants that generated by motor vehicle emissions is carbon monoxide (CO). CO gas can cause health problems for humans, even if exposed to long periods time will cause death. Emission test devices have been widely available in many auto repair shops, but at the moment emission testing, only read gas source or emissions sources from the muffler hole. Cabin space usually escaped from checking, whether there is pollution that enters the cabin or not. This final project has a purpose to design a carbon monoxide detector devices which will show the levels of carbon monoxide (CO) into 4 categories of air quality,that are safe, wary, watch out, and danger. System will automatically warning the driver if the gas exceeds the threshold. Microcontroller that used as the central data processing data is microcontroller Atmega 8, by ATMEL and use gas censor TGS 2442. Design begin with a hardware schematic and software design using BASCOM-AVR. Implementation phase include the implementation of the physical device, programs, and censor. Testing phase is done by testing the tool using 3 gas source, that are cigarette smoke, motorcycle exhaust, and car exhaust. The test result showed that the highest error rate on these tool when compared with a comparable gas analyzer scott instruments is 6.46%, with 93.54% accuracy rate. This CO gas monitor hasadvantage easily portable and include three actuators, that are LCD will show the levels of CO gas, buzzer will give warning sound when gas exceeds the threshold, and the vibrating motor provide tactile warning to the user.